Pengaruh Kemandirian Daerah dan Level of Capital Outlay Terhadap Financial Distress: Studi Empiris pada Pemerintahan Daerah Kabupaten dan Kota di Sumatera Barat Periode 2019-2023 - Ali, Irfan Nazar; Arza, Fefri Indra (Universitas Negeri Padang, 2025)
This research examines the influence of regional financial independence and the level of capital outlay on financial distress in district and city governments in West Sumatra for the 2019-2023 period. Financial distress in local governments is an important issue because it affects their ability to provide public services effectively. With a quantitative approach, this research uses secondary data from the Directorate General of Fiscal Balance, Ministry of Finance. The sample was determined using a purposive sampling technique, and a sample of 95 samples was obtained. The analysis was carried out using multiple linear regression with SPSS version 26 software. The research results showed that regional financial independence had a significant positive effect on financial distress. Meanwhile, the level of capital outlay also has a significant positive effect on financial distress.